A variational approach-based method for simulating the post-liquefaction behaviour of soil masses - Montassar, S.; de Buhan, P.; Dormieux, L.; Jellouli, M. (Computational Fluid and Solid Mechanics 2003, 2003)
This chapter proposes a general numerical scheme aimed at stimulating the evolution of a soil subject to a liquefaction phenomenon, the constitutive behavior of which is described by means of a regularized Bingham model. This procedure is based on the combination of a variational principle for the velocity field and a step-by-step time integration algorithm making it possible to follow the geometry changes. A first illustration of the method implemented in a finite element code is also presented in the chapter. The adoption of a Bingham model instead of a Newton model for describing the behavior of the liquefied soil results in increasing the soil resistance and thus limiting the amplitude of geometry change of liquefied soil spreading. Some hypotheses, such as the prefect bonding assumption between the liquefied soil and the substratum can be investigated and replaced by a more realistic boundary condition allowing for possible slippage beyond a certain shear stress level.